2019
DOI: 10.1016/j.jbiomech.2019.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Statistical shape modelling versus linear scaling: Effects on predictions of hip joint centre location and muscle moment arms in people with hip osteoarthritis

Abstract: Marker-based dynamic functional or regression methods are used to compute joint centre locations that can be used to improve linear scaling of the pelvis in musculoskeletal models, although large errors have been reported using these methods. This study aimed to investigate if statistical shape models could improve prediction of the hip joint centre (HJC) location. The inclusion of complete pelvis imaging data from computed tomography (CT) was also explored to determine if free-form deformation techniques coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 36 publications
2
61
0
Order By: Relevance
“…The Musculoskeletal Atlas Project Client 20 containing shape models of the pelvis and lower limbs was used to scale a generic musculoskeletal model (Gait2392) 21 . This approach has been shown to better reflect individual bony geometry compared to traditional linear scaling 15 . The workflow to scale a generic lower‐limb model has previously been described 15 but briefly, scale factors were computed based on the distances between markers on the unscaled model and corresponding embedded anatomical landmarks on the pelvis, femurs, and tibias from the shape model.…”
Section: Methodsmentioning
confidence: 99%
“…The Musculoskeletal Atlas Project Client 20 containing shape models of the pelvis and lower limbs was used to scale a generic musculoskeletal model (Gait2392) 21 . This approach has been shown to better reflect individual bony geometry compared to traditional linear scaling 15 . The workflow to scale a generic lower‐limb model has previously been described 15 but briefly, scale factors were computed based on the distances between markers on the unscaled model and corresponding embedded anatomical landmarks on the pelvis, femurs, and tibias from the shape model.…”
Section: Methodsmentioning
confidence: 99%
“…The body anatomy in the model can be informed by medical imaging [66][67][68] or extracted from population databases [69,70]. Statistical methods have been developed for improving the anatomical fidelity in the model using the limited set of information typically available in a clinical environment [71,72]. Real-time or near real-time numerical methods have been developed to predict muscle and joint force [73], bone strains [74,75] and strength [76].…”
Section: A Perspective Toward Personalized Exercise Prescriptionmentioning
confidence: 99%
“…While medical images are included for scaling, the time for creating a participant-specific model increases (Davico et al, 2020). In marker based scaled models, errors in joint loading or muscle forces (Martelli et al, 2015b) can occur based on soft tissue artifacts (Wesseling et al, 2016) or incorrect defined joint centers (Martelli et al, 2015c;Kainz et al, 2017;Bahl et al, 2019). Moreover, the different definitions of the joints in case of degree of freedom (DoF) or muscle positioning have been shown to influence the outcome (Valente et al, 2014(Valente et al, , 2015.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Previous studies found that the different scaling approaches, e.g., body mass based scaling, scaling based on shape modeling or linear scaling affect the outcome of MSK modeling (Kainz et al, 2017;Bahl et al, 2019). In general, scaling based on medical images or with the inclusion of calculated joint centers into the scaling process improves the accuracy of the calculation of the hip joint center location compared to scaling with surface markers alone (Kainz et al, 2017;Bahl et al, 2019).…”
Section: Limitations Of Musculoskeletal Modelingmentioning
confidence: 99%